PERLINDUNGAN KORBAN TINDAK PIDANA PERDAGANGAN ORANG BERKEDOK PENYALUR TENAGA KERJA - Jaiheno, Gabriela Andriyani; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The criminal act of human trafficking using the mode of providing labor has become a severe problem that affects human rights. The research aims to analyze the effectiveness of victim protection policies in the criminal act of human trafficking under the guise of labor supply in Indonesia. A descriptive normative juridical research type was used. Secondary data is analyzed qualitatively, and conclusions are drawn using deductive logic. The research results show that legal protection for victims of criminal acts of human trafficking has been substantially regulated in law. However, legal provisions were found to have weaknesses, still not accommodating victims' rights and interests and a lack of harmony in the components of the criminal justice system. It is hoped that the results of this research can provide helpful guidance for policymakers, legal practitioners, and other stakeholders to improve efforts to protect victims of human trafficking and its law enforcement.Keywords: criminal act, human trafficking, labor supplier